2010
DOI: 10.1007/s12020-010-9331-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-testicular melatonin injection on testicular functions, local and general immunity of a tropical rodent Funambulus pennanti

Abstract: Local antigonadotrophic action of melatonin in testes has never been correlated with local and general immune status of any rodent. Intra-testicular injection of melatonin (2.5 μg/50 μl) for 10 days (MI-10D) and 20 days (MI-20D) was given to young adult male of Funambulus pennanti and testicular androgen receptor (AR), androgen binding protein (ABP) expression, 3β-hydroxysteroid dehydrogenase (3β-HSD) activity, and Mel1aR expression in thymus was checked along with general immune parameters. Further, immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro. When administered orally at 10 mg/kg bodyweight, melatonin has been described as a counteracting substance for testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Vargas et al, 2011).…”
Section: Discussioncontrasting
confidence: 83%
“…However, in the aforementioned studies melatonin did not have any effect with the doses used in contrary to other reports where melatonin had a protective role in testis and spermatogenesis of rats subjected to intermittent hypobaric hypoxia (Hartley et al, 2009;Bustos-Obregón et al, 2010;Vargas et al, 2011);Ahmad & Haldar (2010) as well as hamsters and rats, where melatonin seems to act directly on Leydig cells to suppress testosterone release in vitro. When administered orally at 10 mg/kg bodyweight, melatonin has been described as a counteracting substance for testis and spermatogenesis damage in rats subjected to intermittent hypobaric hypoxia (Vargas et al, 2011).…”
Section: Discussioncontrasting
confidence: 83%
“…The MT1 receptor expression pattern in the spleen showed significant stimulation in melatonin treated group as was previously noted [17] and was down-regulated in the UVB irradiated squirrels. The loss of normal cellular physiology due to the peroxidation of membrane lipids could be one of the reasons for the suppressed receptor expression since MT1 is associated with the cell membrane.…”
Section: Discussionsupporting
confidence: 80%
“…The spleen being a lymphoid organ has an extensive repertoire of lymphocytes and hence is under strong influence of melatonin which is immune-stimulatory by nature [17]. The results of our study showed a significant increase in the TLC in the melatonin administered squirrels and that pertains to the immune-stimulatory property of melatonin [28].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations